Insecure Attachment Styles and Bullying Perpetrators in the Workplace: An Exploratory Study - Mushtaq, Sadia; Muzaffar, Rubina; Rohail, Iffat (Nurture, 2022)
Purpose: It has been widely debated over the past two decades that workplace bullying harms both victims and organizations equally. However, the perpetrator’s perspective on bullying is an inadequately researched area that has been highlighted by many researchers. This study aims to explore the predictive effect of an insecure attachment (avoidant attachment style and anxious attachment style) on the bullying behavior of perpetrators in the workplace. Methodology: Data is collected from different organizations in Pakistan for this cross-sectional study. The sample size is 203. For the analysis of hypotheses, the SEM model of SmartPLS is used. Findings: The results indicate that an avoidant attachment style positively affects bullying behavior in the workplace. Unlike the anxiety attachment style which has no significant relationship with workplace bullying behavior. Practical implications: These findings highlight the importance of secure attachment for healthy interpersonal relationships and the role of insecure attachment in emerging bullying behaviors in the workplace.